Effect of xylopic acid on alloxan-induced diabetic neuropathy in rats - Ameyaw, Elvis Ofori; Obese, Ernest; Asante, Du-Bois; Biney, Robert P.; Karikari, Akua A.; Adakudugu, Emmanuel A.; Dzotefe, Bright G.; Adanusa, Maddison (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Neuropathic pain is a very disturbing condition commonly found in diabetic patients. This study investigated xylopic acid (XA), the major constituent of Xylopia aethiopica in diabetic neuropathy as well as established possible toxicity of the compound on some selected tissues. Methods: Diabetes was induced in six groups of male rats with 120 mg/kg alloxan monohydrate. Diabetes was confirmed as a blood glucose level >15 mmol/dl. Neuropathic pain was confirmed on day three post-diabetes induction and treatment with 10 mg/kg, 30 mg/kg or 100 mg/kg xylopic acid, 10 mg/kg glibenclamide, 10 mg/kg morphine, and 10 ml/kg normal saline were initiated and continued for the next 15 days. The effects of the treatments on cold allodynia (cold water at 4°C) and thermal hyperalgesia (hot water at 55 ± 1°C) were evaluated within the duration of treatments. Histology of the liver and kidney, as well as haematological, serum biochemical, and semen analyses, were done after the fifteenth day of the experiment. Results: Xylopic acid produced significant anti-hyperglycaemic and analgesic effects in the cold allodynia and thermal hyperalgesia tests. Sperm motility, viability and count were significantly restored at 10 mg/kg XA as compared higher doses and negative control. The outcome of haematological analysis revealed a protective effect of XA although histological damage liver and kidney due to alloxan treatment was observable. Conclusions: Xylopic acid ameliorates diabetic neuropathy in rats and does not exert detrimental effects at low doses.